Primary Cardiac Burkitt Lymphoma Presenting with Abdominal Pain - Dimitrios Tzachanis; Rajan Dewar; Katarina Luptakova; James D. Chang; Robin M. Joyce (Case Reports in Hematology)
We describe the case of a 44-year-old woman with primary Burkitt lymphoma of the heart who presented with abdominal bloating and epigastric discomfort secondary to tamponade physiology caused by a large pericardial effusion. The pericardial fluid contained a large number of highly atypical lymphocytes with moderate basophilic cytoplasm, rare punched-out vacuoles, a vesicular nuclear chromatin, large nucleolus, and marginated chromatin that by FISH were positive for the 8;14 translocation. She had no other sites of disease. She was treated with four alternating cycles of modified CODOX-M and IVAC in combination with rituximab and remains in remission more than 5 years since diagnosis.